PENGARUH PARTISIPASI MAHASISWA PENDIDIKAN IPS DALAM MENGIKUTI PROGRAM KAMPUS MENGAJAR TERHADAP MINAT MENJADI GURU IPS - Ajeng Risti Amaliya; Mamat Ruhimat; Asep Dahliyana (Jurnal Pijar, 2023)
This study focuses on the influence of Kampus Mengajar programme towards interest in becoming social science teacher. The purpose of this study was to analyze the influence of Kampus Mengajar programme towards the interest in becoming social science teacher. The study uses quantitative approach to the descriptive method. This study was conducted in Universitas Pendidikan Indonesia, faculty of social science education, social science education study programme. The sample of this study is active college students from batch 2019 and 2020 who are attended and currently participating in Kampus Mengajar programme. The data was collected using questionnaire. The result showed that (1) there is an influence from social science education students who participate in Kampus Mengajar programme towards interest in becoming social science teacher with tcount (3.965) is greater than ttable (1.66) with significant level of 0.05; (2) there is a quite good participation from social science students in Kampus Mengajar programme towards interest in becoming social science teacher. The conclusion of this study indicate that Kampus Mengajar programme can help increasing social science education students' interest in becoming social science teacher.